1987
DOI: 10.1177/000348948709600203
|View full text |Cite
|
Sign up to set email alerts
|

Reinnervation of Skeletal Muscle: A Comparison of Nerve Implantation with Neuromuscular Pedicle Transfer in an Animal Model

Abstract: In recent years there has been increased interest in the possibility of reinnervating paralyzed muscles, particularly the muscles of the face and of the larynx. There has been dispute over the relative effectiveness of different approaches. This study was undertaken to compare direct nerve implantation with the transfer of a neuromuscular pedicle using denervated strap muscles in a rabbit model. Reinnervation was carried out both immediately after denervation and after a delay period. Evidence of return of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Muscle force measurement is widely used to assess the mechanical function and contractile properties of a muscle [3541]. Our studies [28,3033] and others [23,25,42,43] have demonstrated that force measurement is a reliable technique in determining the degree of functional recovery of a reinnervated muscle. The denervated muscle is characterized by reduced muscle mass, decreased fiber size, increased connective tissue, and reduced metabolic capacity [44,45] which can be reversed by reinnervation [28,33,46].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Muscle force measurement is widely used to assess the mechanical function and contractile properties of a muscle [3541]. Our studies [28,3033] and others [23,25,42,43] have demonstrated that force measurement is a reliable technique in determining the degree of functional recovery of a reinnervated muscle. The denervated muscle is characterized by reduced muscle mass, decreased fiber size, increased connective tissue, and reduced metabolic capacity [44,45] which can be reversed by reinnervation [28,33,46].…”
Section: Discussionmentioning
confidence: 92%
“…The only reconstructive option to reinnervate that muscle is direct nerve implantation (i.e., muscular neurotization) [17,18] or nerve-muscle pedicle (NMP) transfer. The NMP technique has been used for laryngeal [1922] and facial reinnervation [2325]. However, controversy exists concerning the success rate of the NMP method.…”
Section: Introductionmentioning
confidence: 99%
“…In 1980's, Cummings and colleagues applied the NMP technique to facial reinnervation in animal experiments. 72-74 Clearly, this method has been employed primarily to treat paralyzed larynx and face. Up to date, many studies on the NMP reinnervation procedure have been reported in the literature over the past 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators 45,72,73 performed animal experiments to compare direct nerve implantation (DNI) with NMP using strap muscles such as SH and ST in rabbits. They found that neither method had a clear advantage over the other, at least in terms of function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation